Identifying the Links Between Trauma and Social Adjustment: Implications for More Effective Psychotherapy With Traumatized Youth - Ahmadi Forooshani, Sayedhabibollah; Murray, Kate; Khawaja, Nigar; Izadikhah, Zahra (Frontiers in Psychology, 2021)
Background: Past research has highlighted the role of trauma in social adjustment problems, but little is known about the underlying process. This is a barrier to developing effective interventions for social adjustment of traumatized individuals. The present study addressed this research gap through a cognitive model. Methods: A total of 604 young adults (aged 18 to 24; living in Australia) from different backgrounds (refugee, non-refugee immigrant, and Australian) were assessed through self-report questionnaires. The data were analysed through path analysis and multivariate analysis of variance. Two path analyses were conducted separately for migrant (including non-refugee and refugee immigrants) and Australian groups. Results: Analyses indicated that cognitive avoidance and social problem solving can significantly mediate the relation between trauma and social adjustment (p < .05). The model explaining this process statistically fit the data (e.g., NFI, TLI, CFI > 0.95). According to the model, reacting to trauma by cognitive avoidance (i.e., chronic thought suppression and over-general autobiographical memory) can disturb the cognitive capacities that are required for social problem solving. Consequently, a lack of effective social problem solving significantly hinders social adjustment. There were no significant differences among the Australian, non-refugee immigrant and refugee participants on the dependent variables. Moreover, the hypothesized links between the variables was confirmed similarly for both migrant (including refugee and non-refugee immigrants) and Australian groups. Conclusion: The findings have important implications for interventions targeting the social adjustment of young individuals. We assert that overlooking the processes identified in this study, can hinder the improvement of social adjustment in young adults with a history of trauma. Recommendations for future research and practice are discussed.